In the service of… - Preston, Julieanna (Interstices: Journal of Architecture and Related Arts, 2022)
In the service of … recalls ground maintenance, a live art performance enacted at the 2013 Plenitude and Emptiness Symposium, Edinburgh, Scotland. This essay takes the form of a series of letters written to the commercial cleaner who was responsible for maintaining the space on an everyday basis. Invoking an empathy-inducing method to build a relational affinity with the cleaner and her labour, the letters perform a next iteration of caring for the interior space on her behalf, specifically, sweeping the gallery and presentation room over the three-day event. Documented in a video, this durational gesture raised greater awareness of the invisible yet material labour so key to the university’s delivery of learning services and to the ongoing life of the building. It amplified the low-tech spatio-political and material agency of the broom and dirt’s long social history in relation to a woman’s everyday work on the interior’s surfaces of a public architecture.